Prevalência do consumo de cigarro e álcool entre universitários do curso de medicina na cidade de Fortaleza –Ceará - Gomes, Ileana Pitombeira (2018)
Introduction: The consumption of alcohol and tobacco products among young people is very worrying. This consumption stands out among university students, evidencing an additional concern when associated with students in the health area. Objective: To characterize the consumption of tobacco and alcohol among university students of medicine courses in the city of Fortaleza. Methods: A cross-sectional study was carried out with two time-cuts involving students from medical schools in Fortaleza, Ceará, Brazil, through a semi-structured questionnaire containing 46 objective questions. In the first moment, a transversal analytical study was carried out involving students in three different moments of the course (S1 / S2, S7 / S8 and I3 / I4). Subsequently, those students who were taking the first year of the course in the year 2012 were investigated again at the end of the course (year 2016), during the boarding school. Sample was calculated considering as the study population the maximum number of students in the two moments evaluated. Results: a total of 1,035 students were distributed proportionally in the three periods, 392 (37.87%) in the first year (S1-S2), 319 (30.82%) in the fourth year (S7-8) and 324 ) of boarding school (I3-I4). Of the total, 254 (24.6%) had smoked. This consumption was significantly higher among males (p = 0.025). All academics who have tried some substance derived from tobacco have already ingested alcoholic beverage at some time in their lives (p <0.000). Alcohol consumption was reported by more than 80% of students. Tobacco consumption increased from 17.4% during the first year of the course to 28.2% during boarding (p <0.001). The same occurred with alcohol consumption that was already high at the beginning of the course (84.6%) and increased to 92.6% (p <0.001). In the first year of the course 40.5% of the students reported already having gotten drunk at least once. During college this percentage rose to 59.5% (PR = 1.66, p <0.001). Conclusion: The consumption of alcohol and tobacco increased significantly during the course of medicine. There is a need for interventions in the habits of medical students with the objective of reducing the excessive consumption of alcohol and the maintenance of smoking in this population.